Mary Seacole and Mary Soldier: black nurses who made history - Lily Löw; Taka Oguisso (Universidad de Alicante, 2014)
This study aims at giving visibility to two women; Mary Jane Seacole and Mary Soldier, who have experienced racism in their actions, but they knew how to face the unknown boundaries, overcoming them in search of their lives ideals. Through the documental research method, it is intended to rescue the history of these black women, placing them as models for the nursing professional history and also among the forerunners of the modern nursing.